HUBUNGAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DIPONDOK PESANTREN AL-AZIZI KANDANGTEPUS KECAMATAN SENDURO KABUPATEN LUMAJANG - Hasanah, Nikmatul; Alfitri, Rosyidah; Shofa Ilmiah, Widia (NHM PRESS, 2024)
Anemia is a type of disease where the sufferer experiences a lack of hemoglobin levels in the blood. Most of those who experience anemia are women, especially teenagers. Because teenage girls often do not consume food with sufficient nutritional content and experience menstruation every month. Adolescence is also a period of nutritional vulnerability which is caused by various things, such as changes in lifestyle and eating habits of teenagers which will affect their nutritional intake and needs. The purpose of this study was to analyze the correlation between nutritional status and the incidence of anemia in boarding school teenagers. This research method is an analytical survey research using a cross-sectional approach/design. The population is 40 teenagers. The sampling technique used in this research was the Total Sampling technique. The sample for this research was 26 young women in Islamic boarding schools. Data collection using an observation questionnaire. The results of the study showed that 13 people (50%) experienced poor nutritional status, while the remaining 10 people (38%) had normal weight. Some 13 respondents (50%) had HB levels of 10 mg/dl, while the remaining 11% had normal Hb levels of 12 mg/dl. statistical test Pearson correlation statistical test was carried out. The results of the study of 26 respondents showed a significant relationship between nutritional status and the incidence of anemia in adolescents in Islamic boarding schools. The conclusion is that the majority of respondents experienced anemia and did not receive blood supplement tablets, based on statistical tests it was found that there was a relationship between nutritional status and the incidence of anemia in adolescents in Islamic boarding schools.